Design, fabrication and testing of shea nut shelling machine - Ibrahim, M. G.; Shehu, A. A.; Musa, Dauda Solomon; Ahmad, Desa (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Sheanut (Butyrospernum paradoxum) is an oil rich tropical tree crop, which is indigenous to the West African savannah zone. In Nigeria, most of the sheanuts shelling are done manually by rural women and children, which is labour demanding and tedious. This research work was carried out to determine some physical and mechanical properties of sheanut in order to minimize economic losses associated with its processing. The mean values recorded for the physical properties at 25% moisture content (wb) are; major diameter (29.20 mm), intermediate diameter (21.90 mm), minor diameter (15.00 mm), geometric mean diameter (21.90 mm), arithmetic mean diameter (21.20 mm), angle of repose (30.280). The mean values for the mechanical properties are; linear limit force (0.80 kN), linear limit deformation (4.60 mm), bioyield point force (1.40 kN), bioyield point deformation (6.50 mm), rupture point force (2.10 kN) and rupture point deformation (9.60 mm). Based on the physical and mechanical properties, a sheanut shelling machine was developed that is capable of addressing the aforementioned problems. Putting into consideration better shelling and efficient separation of shea nuts so as to encourage more utilization and processing of shea nuts and its products. The machine was designed to be powered by 5 hp electric motor. It was tested to shell, separate and clean sheanuts. The result of the performance evaluation showed that the machine had shelling efficiency of 96%; cleaning efficiency of the machine was 69.56% while the recovery efficiency was 82.7%. The successful development of this machine will reduce drudgery and time taken associated with the traditional method of sheanut shelling and therefore will increase productivity and utilization.